STUDYING THE CAUSES AND CONSEQUENCES OF RESTORATION FAILURE AND POTENTIAL STRATEGIES FOR PREVENTION (Journal of Medical & Health Sciences Review, 2025)
Dental restoration failure is one of the major problems faced in dentistry and results in further treatment requirements, dissatisfaction by the patients, and increased costs. Therefore, a thorough knowledge of causes and consequences of restoration failure is necessary for designing effective preventive measures. Objective: The present study aimed to determine the causes and consequences leading to restoration failure and eventually develop prevention strategies. Methodology: This cross-sectional study was conducted in a dental clinic setting. Dental records of 100 middle-aged patients (25-50 years) from restoration failure were used for the record review study. Standardized Dental Record Extraction Form (SDREF) was used to extract the relevant clinical and demographic data. Patient Satisfaction Questionnaire (PSQ) was used to assess the satisfaction levels of patients with their dental restorations. Descriptive statistics and logistic regression were used for data analysis to determine factors associated with restoration failure.Results: The study reveals that 62% of those restoration failures are due to poor oral hygiene, 22% to inadequate restoration design, and 16% due to material failure. The logistic regression analysis demonstrated that a significant association was found between restoration failure and  poor oral hygiene (OR=2.3, p